2020
DOI: 10.1007/s11356-020-09031-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and occurrence of microplastics in the stomach of commercial fish species from a municipal water supply lake in southwestern Nigeria

Abstract: Microplastics (MPs) are physical anthropogenic pollutants and their ability to act as contaminant vectors in biological matrices is of serious ecosystem and human health concern. In the present study, we have, for the first time, screened and detected MPs in the stomach of a select group of commonly consumed fish species from a municipal water supply lake (Eleyele) in Nigeria. A total of 109 fish samples consisting of eight (8) species: Coptodon zillii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…The small-sized ranged from 0.011 to 0.5315 mm MP abundance was found in the river water bodies; Obiaraedu, Nwangele, Okumpi, Ogbajarajara, and Onuezuze Rivers (Ebere et al 2019 ), Bloukrans River in the eastern periphery of the Mediterranean Sea (Nel et al 2018 ), Bloukrans River (Nel et al 2019 ). The size of MP abundance from the three studied lakes, Oxbow Lake (Biginagwa et al 2016 ), Eleyele Lake (Adeogun et al 2020 ), and Victoria Lake (Oni et al 2020 ) have been recorded as 2.41, 0.827, and < 0.5 mm, respectively. More or less, the estuaries, coastlines, bays, and gulfs of the Mediterranean Sea and the Atlantic Ocean have been observed that a similar length of MP abundance ranged from 0.63 to 2.6 mm.…”
Section: Physical and Structural Characteristics Of Microplastics In The African Water Systemmentioning
confidence: 94%
See 4 more Smart Citations
“…The small-sized ranged from 0.011 to 0.5315 mm MP abundance was found in the river water bodies; Obiaraedu, Nwangele, Okumpi, Ogbajarajara, and Onuezuze Rivers (Ebere et al 2019 ), Bloukrans River in the eastern periphery of the Mediterranean Sea (Nel et al 2018 ), Bloukrans River (Nel et al 2019 ). The size of MP abundance from the three studied lakes, Oxbow Lake (Biginagwa et al 2016 ), Eleyele Lake (Adeogun et al 2020 ), and Victoria Lake (Oni et al 2020 ) have been recorded as 2.41, 0.827, and < 0.5 mm, respectively. More or less, the estuaries, coastlines, bays, and gulfs of the Mediterranean Sea and the Atlantic Ocean have been observed that a similar length of MP abundance ranged from 0.63 to 2.6 mm.…”
Section: Physical and Structural Characteristics Of Microplastics In The African Water Systemmentioning
confidence: 94%
“…These processes have been used to remove interfering organic tissues and inorganic dust also. In this review, the degradation of impurities in the samples was found oxidation with potassium hydroxide (KOH) (Sparks 2020 ; Adika et al 2020 ; Shabaka et al 2020 ; Dahms et al 2020 ), hydrogen peroxide (H 2 O 2 ) (Adeogun et al 2020 ; Oni et al 2020 ; Vilakati et al 2020 ), and sodium hydroxide (NaOH) (Biginagwa et al 2016 ). KOH and H 2 O 2 are most popular and reportedly found in the retrieved literature as well as worldwide used for effective treatment processes as an oxidizing agent.…”
Section: Sampling Techniques Mps Preparations and Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations